Pb immobilization by phosphate-solubilizing fungi and fluorapatite under different Mn2+ concentrations - Zhang, Lei; Guan, Qiang; Yan, Yifan; Sun, Jiahui; Xu, Linyue; Zhang, Shuo; Tian, Da; He, Yue (Frontiers in Microbiology, 2025)
Phosphate-solubilizing fungi (PSF) are commonly employed in the bioremediation of lead contamination through the production of organic acids. However, the secretion of organic acids by PSF is typically affected by various environmental factors. This study investigated the Pb removal process by typical PSF A. niger and P. chrysogenum under different Mn2+ concentrations (0–30 mg/L). The different concentrations of Mn2+ can significantly influence the Pb toxicity tolerance of PSF. PSF A. niger exhibits a stable Pb removal ratio of >99% under different Mn2+ concentrations, much higher than P. chrysogenum <90%. The high concentrations of Mn2+ (15 and 30 mg/L) both inhibited the secretion of organic acids by A. niger and P. chrysogenum. However, 7.5 mg/L Mn2+ can significantly increase the secretion of oxalic acid by A. niger and promote the formation of lead oxalate and pyromorphite. Only 2.25% Pb2+ is released again from the immobilized Pb minerals. Meanwhile, PSF has the highest pyruvate dehydrogenase (PDH) enzyme activities of 31.53 and 17.23 nmol/min/g in 7.5 mg/L Mn2+ treatment. Compared with P. chrysogenum, A. niger is more effective in removing and stabilizing Pb cations. Controlling the appropriate Mn2+ concentration can further improve the Pb bioremediation by PSF.